Implementasi Model Evaluasi Kirkpatrick pada Pelatihan Jarak Jauh Penyuluh Perpajakan: Implementation of Kirkpatrick Evaluation Model in Distance Training of Tax Counselors - Andi Wawan Mulyawan; Azwar, Azwar (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2024)
The objectives of this research are to: (i) evaluate the trainees’s satisfaction on trainers and training performance; (ii) evaluate learning gain or improvement of trainees’s skills, knowledge, and attitude after training; and (iii) know the significant obstacles that can reduce the effectiveness of training. This research used the Kirkpatrick Evaluation Model Level 1 and 2 through questionnaire, interview, and descriptive statistics method and IPA Model. The results reveal that: (1) The overall aspect of the implementation evaluation was assessed by participants in the very good category although it could not meet the level of expectations of participants. On the other hand, the trainers aspect has been able to meet the expectations of participants where the overall level of trainers performance has been assessed by participants and entered into the category of very good; (2) The evaluation component of the implementation for PJJ Penyuluh Perpajakan cannot be considered as a whole where the aspects/components of evaluation are spread in Quadrants I, II and III; (3) All participants get satisfactory scores so that it can be said that the participants have gained additional knowledge, skills, and attitudes after attending the training; (4) In the aspect of organizing, participants generally complain about inadequate internet network quality in some areas. Meanwhile, in the trainer aspect, in general participants give input so that the teachers can multiply the practice and games related to training materials.